EFFECT OF ALKALI TYPE AND DURATION OF NIBS SUBMERSION ON QUALITY OF COCHOLATE POWDER PRODUCED BY “DUTCH PROCESS” METHOD - Meri Juliani; Sigit Mujiharjo; Kurnia Herlina Dewi (Jurnal Agroindustri, 2014)
Purpose of this research was to explain the effect of alkali type and duration of nibs submersion on the quality of chocolate powder.Type of alkalis being tested were Na2CO3(type1)andCa(OH)2 (type2) and the durations were 30, 60, 90 and 120 minutes. Reasearch was done following RCB design with the type of alkali as the block. The nibs was fermented during 6 days, and dried with temperature 115 °C for 6 hours, and applying the Dutch Processmethod topowder the chololate.  Result of the research showed that the treatments were not significantly influence the water content; significantly influence the microba, verysignificantly influence thepH and softness of the powder. Based on the research result; to produce chocolate powder with the best on the fat content was by apllying treatment the type2 alkali with 120 minutes submersion; the best on the fat content was by apllying treatment the type2 alkali with 120 minutes submersion; the best on the fat content was by apllying treatment the type2 alkali with 120 minutes submersion; the best on the fat content was by apllying treatment the type2 alkali with 120 minutes submersion